Stimulation of Language Skills for Early Childhood through the Picture Story Method - Tulasih, Sri; Yussof, Hilmy Baihaqy; Kristiawan, Muhammad (Bulletin of Early Childhood, 2022)
The article analyzed the implementation of learning using the storytelling method through image media and analyzed the obstacles faced in the use of storytelling methods with picture media in developing motivational language skills in early childhood. This research was conducted at the Kindergarten of Sultan Agung Nglanjaran Sardonoharjo Ngaglik Sleman Yogyakarta. The method used the case study method. The research data sources consisted of informants including school principals, class teachers, and students, supported by other sources in the form of documents. Collection data techniques used observation, interviews and documentation. The data analysis is focused during the field process along with data collection. The results found that the development of language skills of students in class B2 elementary school consists of 23 students. There were 40% or 10 students that develop in achieving the indicators, and 60% of children have developed very well in achieving the specified indicators, where as many as 20 students out of 23 students have achieved very good development indicators, and 3 students have started developing.